Global Uncertainty in Moderating Macroeconomics on Banking Stability in Islamic Commercial Banks in Indonesia - Putri Anggraeni, Novita; Nurasri Sudarmawan, Barianto (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
Purpose: This study analyzes the role of the World Uncertainty Index (WUI) in moderating the influence of macroeconomic conditions namely GDP, inflation, and exchange rate on the stability of Islamic banking in Indonesia during 2015 Q1 – 2024 Q4. Method: A quantitative approach was used through multiple linear regression and Moderated Regression Analysis with 40 quarterly data from the Financial Services Authority, Trading Economics, and FRED. Stability was measured using Z scores. Results: Gross Domestic Product and inflation have a significant positive effect on stability with coefficients of β = 0.704421 and β = 0.191898, respectively. The exchange rate is not significant. The World Uncertainty Index has a significant negative effect with β = 18.74672. As a moderator, the World Uncertainty Index strengthens the effect of Gross Domestic Product and exchange rate and weakens the effect of inflation. The R-squared value of 0.771887 indicates a strong explanatory power of the model. Implications: The results of the study emphasize the need for adaptive macroprudential policies to maintain the stability of Islamic banking amid increasing global uncertainty. Originality: This study contributes by including global uncertainty as a moderating variable, thereby broadening the understanding of the determinants of Islamic banking stability.